METHODOLOGICAL GUIDELINES FOR PREPARING SUBMISSIONS FOR THE FORENSIC INVESTIGATION OF FIRE AND EXPLOSION INCIDENTS DURING TANK TRUCK LOADING/UNLOADING OF PETROLEUM PRODUCTS (Part 1) - I. Taubkin (Теория и практика судебной экспертизы, 2015)
The paper offers an overview of data used in the forensic engineering investigations of fires and explosions, as well as relevant laws and regulations, and analyzes the preconditions that lead to fires and explosions at loading racks.